THE INFLUENCE OF PREVENTION FACTORS BY MOTHERS ON TODDLERS WITH DIARRHEA IN THE LAMPULO COMMUNITY HEALTH CENTER, BANDA ACEH CITY - Julisman, Julisman; Naimah, Naimah; Andria, Dedi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2025)
Background: Diarrhea is a disease that occurs when there is a change in stool consistency other than the frequency of bowel movements. A person is said to have diarrhea if their stools are more watery than usual, or if they have three or more episodes of loose stools within 24 hours that are non-bloody. Method: This research is analytical descriptive in nature, conducted from January 25 to February 20, 2019, at Lampulo Community Health Center. The study sample consisted of 76 mothers with toddlers. Primary data were obtained through interviews with the respondents, while secondary data were collected from Lampulo Community Health Center in Banda Aceh. Data processing was done using SPSS software, with statistical analysis employing non-parametric tests such as Chi-square, analyzed both univariately and bivariately. Result: There was no significant relationship found regarding access to clean water (p value = 0.558), sanitation facilities (p value = 0.238), breastfeeding practices (p value= 0.410), and handwashing habits (p value = 1.000). However, there was a significant association with immunization status (p value = 0.021). Recommendation: It is recommended that mothers regularly participate in all activities organized by integrated health posts (Posyandu), follow medical advice and treatment provided by healthcare providers at Community Health Centers (Puskesmas) to support optimal recovery. Regular health check-ups during these sessions are crucial for maintaining the health of toddlers.